(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The gastrointestinal disease Helicobacter pylori causes includes chronic antral gastritis, gastric ulcers, duodenal ulcers, gastric adenocarcinomas, and non-lymphoma. The majority of infected patients are still asymptomatic. It is well recognised that pathogenicity factors like the proteins encoded by the cagA and vacA genes influence the appearance of disease. Objective: To find the incidence of H.pylori by Rapid urease test. Methods: Study area: Surgery department of Meenakshi medical college hospital and research institute. Study design : Cross-sectional. Study sample: 100 patients Study population: Patients with complaints of chronic abdominal or epigastric pain and willing to undergo upper GI endoscopy. Results: RUT testing can also be done and is especially helpful in difficult diagnostic situations when the physician would like to start treatment soon. As such biopsies for RUT are often taken in patients with recent upper gastrointestinal bleeding. In this situation, there may be an increased prevalence of false negative results. False negative tests are also common after partial gastrectomy probably because of reduced bacterial load often related to the presence of bile. As such false negative results have little clinical importance unless they are accepted as proof of the absence of an H. pylori infection.